A Reliability Study of Multiplanar Radiographs for the Evaluation of SNAC Wrist Arthritis. (May 2022) - Saltzman, Eliana B.; Wahl, Elizabeth P.; Fletcher, Amanda N.; Said, Nicholas; Mithani, Suhail K.; Klifto, Christopher S.
Background: Scaphoid nonunion advanced collapse (SNAC) is a common form of wrist arthritis, the treatment of which depends on the arthritic stage. The Vender classification serves to describe SNAC arthritis based on a single posteroanterior (PA) radiograph. The purpose of this study was to evaluate the intraobserver and interobserver agreement of the Vender classification, comparing multi versus single radiographic views.Methods: A retrospective review of patients with SNAC arthritis who underwent a proximal row carpectomy or a 4-corner fusion was performed. The included patients had 3 radiographic views of the pathologic wrist. Fifteen patients were analyzed by 5 blinded reviewers. Wrists were graded using the Vender classification first on the PA view and then using multiview radiographs. The intraobserver and interobserver agreement was determined using weighted kappa analysis. χ 2 tests were calculated comparing the evaluation between single- versus multiview radiographs and determining a higher Vender stage.Results: Multiview radiographs demonstrated a higher intraobserver κw compared with single-view radiographs (0.72 vs 0.66), both representing substantial agreement. The average interobserver agreement was moderate (κw of 0.48) for single view and slight (κw of 0.30) for multiview evaluation. Evaluating multiview radiographs was 6.37 times more likely to demonstrate Vender stage 3 arthritis compared with single view (odds ratio = 6.37 [confidence interval, 3.81-10.64], P < .0001).Conclusion: Reviewing multiview radiographs more commonly yielded Vender stage 3 osteoarthritis classification. The decreased interrater reliability in the multiview analysis is likely related to the increased number of articular surfaces evaluated. Using a single PA view may underestimate the severity of arthritis present.